Physical activity in the creative learning of adolescents - Hidalgo-Villamil, Ricardo José; Bran-Cepeda, Hilda Cruz (International research journal of management, IT and social sciences, 2024)
In the educational context, the use of physical activity as a teaching resource to generate creative learning in adolescents is commonly ignored by teachers, wasting the opportunity that, through body movement, the student can acquire significant knowledge for his life. In this context, the objective of the research was to analyze the incidence of physical activity on the creative learning of adolescents. The quantitative approach was used by collecting quantitative data and its analysis was carried out with the help of computer and statistical tools that showed the reality of the management of physical activities. A population of 129 students was considered the General Baccalaureate of the Gonzalo Abad Grijalva Educational Unit in the city of Chone, province of Manabí – Ecuador. The Results demonstrate a relevant connection between physical activity and the development of thinking skills, obtaining that the strengthening of interpersonal relationships between students, the relaxation of the body, and the promotion of health care, constitute a path for the development of creativity in the acquisition of interdisciplinary knowledge in the educational process.